131k views
1 vote
3c-2(c+10)=7c-5(c+2)

User Dyo
by
6.4k points

1 Answer

1 vote

Answer: C= -10

Step-by-step explanation: First step: simplify both sides of the equation

3c−2(c+10)=7c−5(c+2)

3c+(−2)(c)+(−2)(10)=7c+(−5)(c)+(−5)(2) (Distribute)

3c+−2c+−20=7c+−5c+−10

(3c+−2c)+(−20)=(7c+−5c)+(−10) (Combine Like Terms)

c + -20 = 2c - 10

c - 20 = 2c - 10

Step 2: Subtract 2c from both sides

c - 20 - 2c = 2c -10 - 2c

−c−20=−10

Step 3: Add 20 to both sides

−c−20+20=−10+20

−c=10

Step 4: Divide both sides by -1

-c/-1 = 10/-1

C=-10

User Oivindth
by
5.9k points